Pharmacognostic Studies and Anti-Bacterial Activity of Fagonia schweinfurthii Hadidi - Naik, Archana A. (International Journal of Pharmaceutical & Biological Archive, 2017)
Fagonia schweinfurthii Hadidi is a small spiny herb growing in dry rocky areas of world which is known in scientific and folkloric literature due to its medicinal uses. The present paper deals with pharmacognostic studies and anti-bacterial activity of F. schweinfurthii Hadidi. Pharmacognostic studies and anti-bacterial activity was carried out from the shade-dried whole plant material of F. schweinfurthii which was found to be good source of alkaloids, tannins, carbohydrates, starch, terpenoids, saponins and mucilage whereas steroids and anthraquinones were absent. Physico-chemical evaluation for ash analysis, percent extractive and moisture content was carried out. These findings will be useful towards establishing purity and quality as well as standardization, authentication of the plant powder, which is gaining relevance in plant drug research. The powdered drug was extracted polarity wise in various solvents, tested against various bacterial strains namely Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli, Staphyloco-ccus aureus, Klebsiella pneumoniae and Salmonella typhimurium. Some of the extracted fractions of the plant exhibit significant anti-bacterial activities which revealed that F. schweinfurthii have an excellent anti-bacterial activity.